2021
DOI: 10.3389/fmed.2021.722614
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy in Acute Promyelocytic Leukemia: Can We Go Beyond Supportive Care?

Abstract: Acute promyelocytic leukemia (APL) is characterized by frequent complications due to a distinct coagulopathy. While advances in treatments have improved long-term survival, hemorrhagic and thrombotic complications remain the most common causes of death and morbidity. Improved understanding of the mechanisms of the coagulopathy associated with APL may lead to therapeutic interventions to mitigate the risk of hemorrhage and thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 84 publications
0
25
0
5
Order By: Relevance
“…El sangrado macroscópico estuvo presente en el 81% de los pacientes al momento del diagnóstico, siendo más frecuente por piel y mucosas, seguido por el sangrado ginecológico y del tracto gastrointestinal. Cuatro pacientes murieron como causa directa del sangrado, siendo la hemorragia en el SNC la causa más frecuente de muerte en nuestra cohorte, al igual que en otros estudios reportados [5,6,[22][23][24].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El sangrado macroscópico estuvo presente en el 81% de los pacientes al momento del diagnóstico, siendo más frecuente por piel y mucosas, seguido por el sangrado ginecológico y del tracto gastrointestinal. Cuatro pacientes murieron como causa directa del sangrado, siendo la hemorragia en el SNC la causa más frecuente de muerte en nuestra cohorte, al igual que en otros estudios reportados [5,6,[22][23][24].…”
Section: Discussionunclassified
“…La hemorragia intracraneal es la principal complicación hemorrágica y la causa más frecuente de muerte prematura [5]. Por otra parte, la trombosis venosa y arterial (embolia pulmonar, infarto de miocardio y eventos cerebrovasculares isquémicos), a pesar de que puede pasar desapercibida debido a su baja incidencia en comparación con los trastornos hemorrágicos [5,6], se presenta en el 5% a 20% de los pacientes [6].…”
Section: Introductionunclassified
“…Unlike VMTD or macrothrombosis, fibrin clot disease should be defined as true clotting disorder (coagulopathy) made of fibrin clots within intravascular space as seen only in APL without an intravascular injury. The patient with APL [ 58 , 59 , 60 ] was found to overexpress TF in leukemic promyelocytic cells. When TF activates FVII and form TF-FVIIa complex, TF path ( Figure 1 ) promotes sequential activation of coagulation proteins and serine proteases via the extrinsic clotting cascade, which is not detailed in the Figure because this coagulation scheme is well known.…”
Section: Current Classification Of Thrombotic Disorders Without Molec...mentioning
confidence: 99%
“…ATRA may act on the coagulation-anticoagulation system through the following mechanisms: (1) ATRA has a role in APL cell secretion of related cytokines and surface proteins: ATRA decreases APL cell expression of cellular procoagulants (CP and TF) that activate the coagulation cascade and inhibits coagulation pathway activation; ATRA also increases APL cell expression of urokinase-type plasminogen activator (u-PA), tissue-type plasminogen. 9 (2) Major effects of ATRA on vascular endothelial cells and monocytes: ATRA induces the expression of thrombomodulin (TM) in endothelial cells (EC), a membrane receptor that binds to and inactivates thrombin; the protein C/protein S system is then activated by the TM/thrombin complex, a potent anticoagulation mechanism; ATRA inhibits EC and mononuclear phagocyte-exposed tissue procoagulant TF expression; ATRA induces t-PA and a small amount of PAI-1 production by EC and promotes endothelial cell fibrinolytic response; ATRA counteracts the prothrombotic effect of cytokines tumor necrosis factor-α (TNF-α) and interleukin 1b (IL-1b) on EC. 18 (3) ATRA on platelet action: One study investigated the effects of ATRA on platelet function by incubating human platelets with different doses of ATRA and found that ATRA inhibited platelet aggregation, proliferation, clot contraction, and impaired in vivo hemostatic processes and arterial thrombosis after ATRA treatment.…”
Section: Atramentioning
confidence: 99%